Implementasi Kebijakan Ekonomi Biru Indonesia dalam Kerangka Integrasi Ekonomi ASEAN - Rara Gusnita Putri; Simon Sumanjoyo Hutagalung; Irsyaad Suharyadi (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2026)
Indonesia possesses abundant marine resources and has increasingly promoted the blue economy as a key pillar of sustainable development. At the same time, ASEAN economic integration has created broader opportunities for intra-regional trade, including the expansion of Indonesia’s maritime exports to the Philippines, one of the most promising markets in Southeast Asia. This study aims to analyze the implementation of Indonesia’s blue economy policy in strengthening maritime product exports to the Philippines within the framework of ASEAN economic integration. The research employs a qualitative approach through literature review and document analysis of government policies, trade reports, publications from international organizations, and relevant academic literature. The findings indicate that the implementation of the blue economy contributes to enhancing the competitiveness of maritime products through sustainable marine resource management, downstream industry development, and value-added processing of fisheries and marine commodities. Furthermore, ASEAN economic integration provides opportunities through improved trade connectivity, regulatory harmonization, and the development of regional supply chains that facilitate Indonesia’s access to the Philippine market. Nevertheless, several challenges remain, including non-tariff barriers, increasingly stringent sustainability standards, and limitations in maritime logistics infrastructure. The study concludes that the synergy between Indonesia’s blue economy policy and ASEAN economic integration can serve as an effective strategy for strengthening maritime exports to the Philippines while simultaneously promoting sustainable economic development.